Metabolome-wide association study of four groups of persistent organic pollutants and abnormal blood lipids. (March 2023) - Chen, Yiran; Lv, Jiayun; Fu, Lei; Wu, Yan; Zhou, Si; Liu, Shiwei; Zheng, Linjie; Feng, Wenru; Zhang, Lin
Graphical abstract: Highlights: Serum PFAS levels were associated with higher risk of abnormal TC and LDL. Potential biomarkers that intermediate the association between PFASs and abnormal cholesterol were identified. Mechanisms linking PFASs to abnormal cholesterol may mainly involve primary bile acid biosynthesis, glycerophospholipid metabolism and linoleic acid metabolism. PPARγ likely play a role in the associations between PFASs and abnormal cholesterol metabolism. Metabolites associated with 6:2Cl-PFESA and 8:2Cl-PFESA were identified, and 6:2Cl-PFESA was associated with the fewest metabolites than other PFAS. Abstract: Environmental exposure increases the risk of dyslipidemia, which affects human health. Research has shown that persistent organic pollutants (POPs), including per- and polyfluoroalkyl substances (PFASs), polychlorinated biphenyls, polybrominated diphenyl ethers, and phthalate metabolites, are associated with a higher risk of abnormal blood lipid levels in humans. However, the key molecules involved in dyslipidemia and the mechanisms are not fully understood. This study aims to investigate the biomarkers that mediate the relationships between blood lipids and four groups of POPs and revealed their potential mechanisms. Specifically, in 278 male blood samples, blood lipid and POPs levels were measured and metabolites were detected using untargeted metabolomics. Spearman's correlation analysis and binary logistic regression were employed to assess the relationship between POPs and lipid indexes. We observed that PFASs were associated with a higher risk of abnormal total cholesterol (TC) and low-density lipoprotein (LDL), while other POPs displayed little association with abnormal lipid indexes. Among all the PFASs, 6:2Cl-PFESA was associated with the fewest metabolites. A metabolome-wide association study combined with a meet-in-the-middle approach was used to identify potential biomarkers that mediate the association between POPs and abnormal blood lipids. The mediation analysis pointed to 105 significant mediators as potential biomarkers mediating the association between PFASs and TC, and 82 significant mediators were potential biomarkers that mediated the association between PFASs and LDL. 24-Hydroxycholesterol, 3alpha, 7alpha-dihydroxy-5beta-cholestan-26-al, PC(18:0/0:0), PC(22:5/0:0), GPCho(18:1/18:1), LysoPC(22:2(13Z, 16Z)), LysoPC(16:0), 9(S)-HODE, 9, 10-DHOME, l -glutamate, 4-hydroxybutyric acid, cytosine, PC(14:1(9Z)/18:0), sphinganine, and (S)-beta-aminoisobutyrate were identified as important biomarkers. The mechanism may mainly involves glycerophospholipid metabolism, primary bile acid biosynthesis, and linoleic acid metabolism. PPARγ likely plays a role in the associations between PFASs and abnormal cholesterol metabolism. Overall, our study provides clues for the early detection of PFAS-induced dyslipidemia and brings forth a theoretical framework for further research into this mechanism.